Computed Tomography-Based Bone Mineral Density Estimation, Duration of Chronic Steroid Exposure, and Incidence of Insufficiency Fractures - Muhammad Moueen, Asim Naeem, Wahid Bakhsh, Ali Raza, Habib Ullah, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic corticosteroid therapy is a major cause of secondary osteoporosis and skeletal fragility, predisposing patients to insufficiency fractures even in the absence of major trauma. In many clinical settings, bone mineral density assessment is not routinely performed, resulting in delayed diagnosis of steroid-related bone loss. Computed tomography-based vertebral attenuation measurement has emerged as a practical opportunistic method for estimating bone mineral density and identifying patients at risk of fracture. Objective: To evaluate the association between computed tomography-based bone mineral density estimation, duration of chronic steroid exposure, and the incidence of insufficiency fractures in adult patients undergoing routine computed tomography imaging. Methods: This retrospective cross-sectional study was conducted at Avicenna Medical College and Hospital and PAF Hospital from June 2022 to June 2023. A total of 100 adult patients with documented chronic corticosteroid use and available computed tomography scans were included. Bone mineral density was estimated using vertebral trabecular attenuation measured in Hounsfield Units. Duration of steroid exposure and the presence of insufficiency fractures were recorded. Statistical analysis was performed using SPSS version 26.0, and a p-value less than 0.05 was considered significant. Results: The mean age of patients was 55.9 ± 13.2 years, and 61.0% were female. The mean vertebral attenuation was 114.7 ± 36.2 Hounsfield Units. Insufficiency fractures were identified in 31.0% of patients. Patients with fractures had significantly lower attenuation values compared with those without fractures (81.3 ± 22.5 vs 129.8 ± 28.4 Hounsfield Units; p < 0.001). Fracture incidence was 14.3% in patients with steroid exposure of 3–12 months and 43.1% in those with exposure exceeding 12 months. Patients with attenuation values below 100 Hounsfield Units had the highest fracture prevalence (64.7%). Multivariate analysis showed that steroid exposure >12 months and attenuation <100 Hounsfield Units were independent predictors of insufficiency fractures. Conclusion: Reduced computed tomography-derived bone density and prolonged corticosteroid exposure are strongly associated with insufficiency fractures. Opportunistic bone mineral density estimation on routine computed tomography may serve as an effective and practical tool for early identification of high-risk patients and prevention of fracture-related complications. Keywords: Computed tomography, bone mineral density, corticosteroids, insufficiency fractures, osteoporosis, Hounsfield units.